The explict formula for the number of the distinct fuzzy subgroups of the cartesian product of the dihedral group 2n with a cyclic group of order eight, where n>3 (2020)
In this paper, the explicit formulae is given for the number of distinct fuzzy subgroups of the cartesian product of the dihedral group of order 2n with a cyclic group of order 8, where n>3.